ERBB3-mediated regulation of Bergmann glia proliferation in cerebellar lamination - Sathyamurthy, Anupama (Development, 2015)
Cortical lamination is crucial for the assembly of cerebellar circuitry. In this process, granule neurons (GNs) migrate along Bergmann glia (BG), which are specialized astroglial cells, from the external granule layer to the internal granule layer. However, the molecular mechanisms underlying BG development are not well understood. Here, we show that GFAP::Cre;Erbb3(F/F) mice, which lack Erbb3 in both radial glia and neurons, exhibit impairments in balance and motor coordination. Cerebellar lamination is aberrant, with misplaced Purkinje neurons and GN clusters. These phenotypes were not observed in Math1::CreER(T2);Erbb3(F/F) mice, where the Erbb3 gene was deleted in GNs, suggesting involvement of non-neuronal Erbb3 in cerebellar lamination. Mechanistic studies indicate that ERBB3 is crucial for the proliferation of BG, which are required for GN migration. These observations identify a crucial role for ERBB3 in cerebellar lamination and reveal a novel mechanism that regulates BG development.